THE USE OF GUIDING QUESTIONS TECHNIQUE TO IMPROVE WRITING SKILL AT THE EIGHTH STUDENTS OF SMP NEGERI 35 MAKASSAR - Festi Frilia; Nurfaizah Sahib; Muliati (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2023)
The purpose of this study was to determine the use of guiding questions technique in improvement students' writing skills of class VIII at SMPN 35 Makassar. This study used the method of quantitative experimental. This study was conducted in three steps such as pre-test, treatment, and post-test. The subjects of this study were students of class VIIl-6 with a total sample of 26 students. Data was collected by giving a descriptive text writing test. Based on the results of data analysis, the students' pre-test results were 42.12 then after receiving treatment the student's score increased to 79.35 in the post-test. Therefore, the hypothesis of this study was accepted. So that the writer concludes that the use of guiding question techniques in writing descriptive texts can improve students' writing skills at SMPN 35 Makassar.